The Spectator, 2016-04-14 - Spectator, Valdosta State University (Valdosta State University, 2016)
The Spectator. April 14, 2016. Vol 90. No.12. Can You Guess the New SGA Executive Board? Find the Answers Inside -- The Big Question: Will Enough Students Pay to See 2 Chainz -- The Results are in: Q & A with 2016-2017 SGA Exec Board. Retrieved on April 19, 2015 from http://www.vsuspectator.com/.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Keywords: Valdosta State University -- Periodicals